Migration beyond capitalism - Hannah Cross (Cambridge, UK ; Medford, MA Polity Press, 2021)
Harshly exploited migrant labour plays a fundamental role in the political economy of contemporary capitalism. The abstract and utopian theorising of many liberals and leftists on the migration question often ignores or downplays patterns of displacement and brutal class dynamics, which divide and weaken working people while empowering the ruling class.
Includes bibliographical references and index
Keywords: Foreign workers